2020
DOI: 10.3892/ijo.2020.5070
|View full text |Cite
|
Sign up to set email alerts
|

Digitoxin inhibits HeLa cell growth through the induction of G2/M cell cycle arrest and apoptosis in vitro and in vivo

Abstract: Cervical cancer is the fourth most common gynecological malignancy affecting the health of women worldwide and the second most common cause of cancer-related mortality among women in developing regions. Thus, the development of effective chemotherapeutic drugs for the treatment of cervical cancer has become an important issue in the medical field. The application of natural products for the prevention and treatment of various diseases, particularly cancer, has always attracted widespread attention. In the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…CDK1, an essential kinase regulating cell cycle progression, is upregulated in multiple cancers. CDK1 depletion promote cell-cycle arrest and ultimately inhibit tumor cell proliferation ( 42 44 ). Additionally, p62 is an adapter that is widely involved in protein interactions.…”
Section: Discussionmentioning
confidence: 99%
“…CDK1, an essential kinase regulating cell cycle progression, is upregulated in multiple cancers. CDK1 depletion promote cell-cycle arrest and ultimately inhibit tumor cell proliferation ( 42 44 ). Additionally, p62 is an adapter that is widely involved in protein interactions.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the proportion of cells in the S/G2-phase might imply DNA damage. In a study on HeLa cells by Gan et al, 2020, they found digitoxin to cause cell arrest in G2 due to DNA double strand breaks [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the high resistance of senescent hMESCs to ouabain is not consistent with proposed selective cytotoxic (senolytic) activity of cardiac glycosides in relation to senescence 14 , 15 . Note that there is a lot of data in the literature that cardiac glycosides also kill high proliferating cancer cells, but not cells that normally cycle 55 59 . The question arises as to what may underlie the selective toxic effect of cardiac glycosides on senescent or cancer cells, and whether disturbances in cell ion homeostasis (in particular, K + content) can be involved in the anti-aging or anticancer effects of these drugs.…”
Section: Discussionmentioning
confidence: 99%